2022
DOI: 10.1155/2022/5314105
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Safety of Glycosides of Tripterygium wilfordii Combined with Renin-Angiotensin System in the Treatment of IgA Nephropathy: A Systematic Review and Meta-Analysis

Abstract: Background. IgA nephropathy (IgAN) is currently the most common primary glomerular disease, accounting for approximately 36.7% to 58.2% of primary glomerular disease in kidney biopsies in China. Definitive diagnosis depends on immunopathological examination of the kidney. The prognosis of this disease was generally considered to be good, but recent studies have found that about half of patients can progress to end-stage renal disease within 30 years of onset. Because the pathogenesis is unknown, there is no sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…To date, he has not undergone rituximab treatment, but he has taken some Chinese herbal medicines, such as Tripterygium wilfordii , which is usually used to cure rheumatoid arthritis, nephrotic syndrome, and systemic lupus erythematosus by doctors in traditional Chinese medicine. Tripterygium wilfordii has a variety of pharmacological and immunomodulatory effects, including anti-cancer, anti-inflammatory, immunosuppressive, anti-fertility, anti-viral, and anti-microbial effects [ 25 , 26 ]; however, its specific effects still need further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, he has not undergone rituximab treatment, but he has taken some Chinese herbal medicines, such as Tripterygium wilfordii , which is usually used to cure rheumatoid arthritis, nephrotic syndrome, and systemic lupus erythematosus by doctors in traditional Chinese medicine. Tripterygium wilfordii has a variety of pharmacological and immunomodulatory effects, including anti-cancer, anti-inflammatory, immunosuppressive, anti-fertility, anti-viral, and anti-microbial effects [ 25 , 26 ]; however, its specific effects still need further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%